Socio-Psychological Crisis in Russia in the Turn of 1970-1980-ies: “Witch Hunt” - E. V. Spitsina (Tsentr nauchnykh i obrazovatelnykh proektov, 2017)
The article is devoted to the study of social consciousness in Russia during the political crisis of the late 1870-ies - early 1880-ies. Considering the social aspect of the crisis, the author pays special attention to the study of such characteristic trend in the crisis time as the exacerbation of social anxiety. Basing on official documents of the police department and the memoirs and testimonies of contemporaries, the author concludes that a marker of the rise of social disintegration was the anti-terrorist fever raged at this time in different strata of society. Its manifestations were not only the growth of mutual suspicion and widespread search for enemies of the existing state system, but also such phenomena of social life, as the proliferation of snitching, gossips going to the masses, and slanderous statements made in the mercenary purposes. The analysis of the manifestations of this kind of “witch hunt” helped to identify its dual social function. In terms of socio-political turmoil, the persecutions served as a simple way to make order in experiencing dissociation and at the same time offered opportunities for successful personal adaptation to it, allowed to derive personal benefits when one is ready to actively follow up the role settings and is able to take advantage of the situation.